Production and the Probabilities of Cost - Nichol, A. J. (Quarterly Journal of Economics, 1942)
Costs calculated in terms of probability, 69. — Deriving particular specifications of supply from given probabilities of cost: initial conclusions, 71. — More complex conditions: dispersion and skewness of cost expectations, 74; variations in dispersion, 78; in skewness, 85; in both, 86. — Influence of dispersion and skewness on monopoly, 86. — "Marginal probability of net revenue, " and "marginal production risk, " 87. — Conclusions, 88.